A multi-ethnic genome-wide association study implicates collagen matrix integrity and cell differentiation pathways in keratoconus - Hardcastle, Alison J; Liskova, Petra; Bykhovskaya, Yelena; McComish, Bennet J; Davidson, Alice E; Inglehearn, Chris F; Li, Xiaohui; Choquet, Hélène; Habeeb, Mahmoud; Lucas, Sionne E M; Sahebjada, Srujana; Pontikos, Nikolas; et al. (Communications biology, 2021)
Keratoconus is characterised by reduced rigidity of the cornea with distortion and focal thinning that causes blurred vision, however, the pathogenetic mechanisms are unknown. It can lead to severe visual morbidity in children and young adults and is a common indication for corneal transplantation worldwide. Here we report the first large scale genome-wide association study of keratoconus including 4,669 cases and 116,547 controls. We have identified significant association with 36 genomic loci that, for the first time, implicate both dysregulation of corneal collagen matrix integrity and cell differentiation pathways as primary disease-causing mechanisms. The results also suggest pleiotropy, with some disease mechanisms shared with other corneal diseases, such as Fuchs endothelial corneal dystrophy. The common variants associated with keratoconus explain 12.5% of the genetic variance, which shows potential for the future development of a diagnostic test to detect susceptibility to disease.
Keywords: buněčná diferenciace; celogenomová asociační studie; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; Extracellular Matrix; studie případů a kontrol; genetické lokusy; jednonukleotidový polymorfismus; rizikové faktory; Phenotype; extracelulární matrix; lidé; kolagen; Australia; Europe; Collagen; Keratoconus; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; Cell Differentiation; Genome-Wide Association Study; keratokonus; Risk Assessment; Austrálie; hodnocení rizik; Genetic Loci; Evropa; Risk Factors